Oncogenic viruses and chemoresistance: What do we know?. (August 2021) - Sadri Nahand, Javid; Rabiei, Nikta; Fathazam, Reza; Taghizadieh, Mohammad; Ebrahimi, Mohammad Saeid; Mahjoubin-Tehran, Maryam; Bannazadeh Baghi, Hossein; Khatami, AliReza; Abbasi-Kolli, Mohammad; Mirzaei, Hamid Reza; Rahimian, Neda; Darvish, Maryam; et al.
Abstract: Chemoresistance is often referred to as a major leading reason for cancer therapy failure, causing cancer relapse and further metastasis. As a result, an urgent need has been raised to reach a full comprehension of chemoresistance-associated molecular pathways, thereby designing new therapy methods. Many of metastatic tumor masses are found to be related with a viral cause. Although combined therapy is perceived as the model role therapy in such cases, chemoresistant features, which is more common in viral carcinogenesis, often get into way of this kind of therapy, minimizing the chance of survival. Some investigations indicate that the infecting virus dominates other leading factors, i.e., genetic alternations and tumor microenvironment, in development of cancer cell chemoresistance. Herein, we have gathered the available evidence on the mechanisms under which oncogenic viruses cause drug-resistance in chemotherapy. Graphical Abstract: ga1